2000
DOI: 10.1128/aac.44.5.1168-1173.2000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Resistance to Streptogramin A Type Antibiotics on the Activity of Quinupristin-Dalfopristin In Vitro and in Experimental Endocarditis Due to Staphylococcus aureus

Abstract: We evaluated the activity of quinupristin-dalfopristin (Q-D) against three clinical strains of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 23 publications
(30 reference statements)
0
31
0
1
Order By: Relevance
“…Zarrouk et al (36) reported that the staphylococcal strains resistant to A compounds but susceptible to B compounds remain susceptible to mixtures in vitro and in vivo. According to our previous (19) and present results, this is true when the strains carry vgaAv alone but not when they carry three SGA r genes.…”
Section: Discussionmentioning
confidence: 99%
“…Zarrouk et al (36) reported that the staphylococcal strains resistant to A compounds but susceptible to B compounds remain susceptible to mixtures in vitro and in vivo. According to our previous (19) and present results, this is true when the strains carry vgaAv alone but not when they carry three SGA r genes.…”
Section: Discussionmentioning
confidence: 99%
“…The Q-D dosing regimen provided areas under the curve for quinupristin and dalfopristin comparable to those achieved in humans after intravenous injection of 7.5 mg of Q-D/kg (6,8). The vancomycin regimen produced peak (40 Ϯ 8 g/ml) and trough (12 Ϯ 5 g/ml) levels in serum comparable to those recommended for humans with severe infections (18).…”
mentioning
confidence: 68%
“…Indeed, a synergistic interaction has previously been reported between Q-D and ␤-lactams in vitro and in vivo (17). The combination of Q-D and vancomycin against strains of MRSA might therefore be of clinical interest in order to increase the bactericidal activity of Q-D and to decrease the risk of emergence of resistance to both antibiotics since strains resistant to Q-D have been selected in vivo (18). Moreover, studies done in vitro (12) and in an infected fibrin clot model study (11) suggested the benefit of this combination.…”
mentioning
confidence: 99%
See 2 more Smart Citations